Navigating ambivalence and exile: a multidimensional analysis of migration in Amitav Ghosh’s The Shadow Lines - Prima, Karima Khatun (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2024.